Governing Uranium in Pakistan - Maria Sultan; Mohammad Riaz Jaspal; Jawad Hashmi; Asra Hassan; Malik A. Ellahi (Danish Institute for International Studies (DIIS), 2015)
Pakistan has three operating nuclear power plants and two under construction with another two planned. Although not a global player in the uranium market with small production figures (around 40 tonnes of uranium per year), Pakistan is revitalising its uranium exploration efforts and plans to significantly increase the share of nuclear energy in its domestic power generation. [...] This report contextualises Pakistan's dual search for energy as well as military security as it mastered the front-end of the nuclear fuel cycle. While information specific to uranium governance is limited in Pakistan given the highly classified nature of the programme, the report provides a substantial sense of the organisational and management of Pakistan's nuclear programme, its legislation and work of the regulator in overseeing the front and back end of Pakistan's nuclear infrastructure. The Pakistan country report is part of the larger global 'Governing Uranium' project on uranium governance, led by DIIS, which seeks to identify governance gaps in uranium accountability and control and provide policy recommendations for improving front-end transparency, security, and regulation.
Keywords: 300